An incurable romantic : the musical journey of Lalgudi Jayaraman - Lakshmi Devnath (HarperCollins Publishers India, 2013)
Lalgudi Gopalaiyar Jayaraman, b. 1930, Indian Carnatic violinist, vocalist and composer.